2018
DOI: 10.3390/ijerph15091888
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Green Public Procurement of Works by Spanish Public Universities

Abstract: Universities play an important role among public institutions because they initiate huge purchasing and contracting activities and contribute to sustainable development through education, research, and day-to-day operations. Existing studies on green public procurement (GPP) practices at Spanish universities focus on products and services. For this study, a total of 316 procedures were collected and analysed from the calls for tenders made by Spanish public universities between 2016 and 2017. The environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…Policies that affect the level of GPP implementation and which of them have the most significant influence on the environmental performance of public entities could be analysed (Testa et al, 2016b). Further research should examine the current state of GPP implementation, provide incentives for the development of tools that encourage GPP (Fuentes- Bargues et al, 2018;Viñé et al, 2013), analyse how the government should be involved in the development of voluntary standards as a starting point in designing public procurement policies (Simcoe and Toffel, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Policies that affect the level of GPP implementation and which of them have the most significant influence on the environmental performance of public entities could be analysed (Testa et al, 2016b). Further research should examine the current state of GPP implementation, provide incentives for the development of tools that encourage GPP (Fuentes- Bargues et al, 2018;Viñé et al, 2013), analyse how the government should be involved in the development of voluntary standards as a starting point in designing public procurement policies (Simcoe and Toffel, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous difficulties related to the GPP were highlighted in the analysed studies. Among them, we mention the lack of clarity of the environmental criteria (Michelsen and de Boer, 2009;Testa et al, 2012;Nissinen et al, 2009), the existence of too generic criteria, which prevents the easy verification by the contracting authority for their compliance (Fuentes-Bargues et al, 2017), the poor presence of environmental criteria in the evaluation of tenders, rarely affecting the awarding decisions (Varnäs et al, 2009;Fuentes-Bargues et al, 2018 ), including them mainly as technical specifications (Testa et al, 2016b). The use of environmental criteria is encountered in the case of national administrations to a greater extent, because they have more resources and better training of personnel on environmental issues (Fuentes-Bargues et al, 2017).…”
Section: Table No 3: Citations Per Yearmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have identified the influence of Digital Division on Big Data generation in the context of green supply chain (Gravili et al, 2018). Another equally important direction was aimed at sustainable public procurement through researches highlighting that the decisions to implement green public procurement have impact on the entire economic and social life, such as: employee satisfaction (Snell, 2006); government initiatives (Steurer et al, 2007); local administration (Preuss, 2009); public and private sectors (Walker and Branner, 2009) and in the academic environment as well (Fuentes- Bargues et al, 2018). Studies on green procurement in the private sector had also been identified, reflecting the interplay of good practices between the public and private sectors (Carter et al, 2000;Appolloni et al, 2014), but also the barriers that may intervene along the way (Giunipero et al, 2012) in the sense of limiting green procurement (Walker et al, 2008;Kaufmann et al, 2012).…”
Section: Review Of the Specialized Literaturementioning
confidence: 99%